UPSHOT OF MARKETING MIX ON CONSUMER PURCHASE DECISIONS AT TRADING COMPANY “UD. ABC” IN SURABAYA - Achmad Daengs GS; Enny Istanti (PT. Mawadaku Sukses Solusindo, 2026)
Companies that implement quality management systems are oriented toward organization, customers, and the market by combining fact-finding and problem-solving approaches. Companies should not merely focus on selling their products, but must also understand consumer needs and wants. Knowledge of consumer behavior is essential for effective marketing practices. Customer satisfaction in marketing should begin with an analysis of consumer behavior based on the evolving situation. This, at the very least, should encourage company managers to determine what marketing activities should be proposed, planned, and executed.Therefore, companies must have marketing tools, commonly referred to as the marketing mix, which includes product, price, place, and promotion. This research uses primary data obtained directly from respondents through questionnaires, and secondary data sourced from the company being studied. The analytical method used in this research is multiple linear regression analysis, with statistical testing using F-test and t-test.The research findings using SPSS software through multiple linear regression analysis show that the F-test result indicates a significant influence between independent variables and the dependent variable, with an F-count value of 22.573 > F-table value of 2.50. For the t-test, it is found that: The product variable (X1) significantly influences consumer purchase decisions (Y) with a t-count of 3.728 > t-table of 1.9944. The price variable (X2) significantly influences consumer purchase decisions (Y) with a t-count of 4.072 > t-table of 1.9944. The place variable (X3) significantly influences consumer purchase decisions (Y) with a t-count of 3.080 > t-table of 1.9944. The promotion variable (X4) significantly influences consumer purchase decisions (Y) with a t-count of 3.230 > t-table of 1.9944.